Clinical Score Predicting Overall Survival After Surgery for Synchronous Metastatic Adrenocortical Carcinoma: A Surveillance, Epidemiology, and End Result-Based Study. Issue 5 (May 2021) - Wu, Kan; Liu, Zhihong; Li, Xiang; Lu, Yiping
Surgery remains the only potential option for prolonging survival in synchronous metastatic adrenocortical carcinoma (ACC). The purpose of this study is to identify patients who may benefit from adrenalectomy. Using the Surveillance, Epidemiology, and End Results (SEER) database (2010-2015), we identified synchronous metastatic ACC patients who underwent adrenalectomy. Cox regression analysis was performed to identify prognostic factors associated with overall survival. A clinical scoring system was created to predict survival after surgery. Sixty-two patients underwent adrenalectomy for synchronous metastatic ACC. Median age was 54.5 years. Median overall survival was 12 months. In univariable analysis revealed that age 65≥years, tumor stage: T3/4, multiple metastases, liver metastases, and no chemotherapy were associated with poor survival. In the multivariable Cox analysis, liver metastases ( P = .017) and no chemotherapy ( P = .039) remained independent predictors of worse prognosis. A clinical scoring system including of 1-point each for the 2 predictors demonstrated good discrimination in predicting survival after adrenalectomy (3-year survival: 45.9% for 0 points and 0% for 1 or 2 points; P < .001, area under the curve = .78). Prolonged survival after adrenalectomy combined with chemotherapy can be potentially achieved in synchronous metastatic ACC patients without liver metastases. Patients with liver metastases should be carefully evaluated for surgery.